JURIDICAL ANALYSIS OF DEBT COLLECTIONS TOWARDS DEFAULT DEBTOR WHICH DEBT HAS MATURED AS THE TIME WHEN THE DEBT ACKNOWLEDGMENT LETTER HAS NOT ENDED - Tommy Leonard; Elvira Fitriani Pakpahan; Helen Jennyver Yang (International Journal of Latin Notary, 2022)
One of the forms of trust between one individual with the others is by making a mutual agreement that is outlined in a written agreement. In the process of it, there are certain conditions that might result in the termination of the agreement as there is default in the written agreement. One of the forms of written agreement that has been stated is debenture note. As if the case of Supreme Court Decision No. 3051/K/Pdt./2017 pertaining to creditor collect debt towards debtor in which the debtor has been negligent and not able to settle the debt throughout 3 (three) months successively as the debt acknowledgment letter has not ended with the result that creditor accuse the debtor to be seized its collateral. Research Methodology that is being used is, juridical normative law research methodology. Inasmuch as juridical normative law research methodology therefore sources and types of data focused on secondary data. Through this research it can be concluded that, debt acknowledgement letter that is made under consideration of Supreme Court Judge is not based on when is the end of the acknowledgement letter, but it is more to the substance of the contents of the debt acknowledgement letter which is the primary essence of the birth of its debt recognition, where both sides agreed the debt shall be collected immediately for 3 (three) months successively.